2021
DOI: 10.3389/fcell.2021.589770
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NR4A Nuclear Receptors to Control Stromal Cell Inflammation, Metabolism, Angiogenesis, and Tumorigenesis

Abstract: The NR4A1–NR4A3 (Nur77, Nurr1, and Nor-1) subfamily of nuclear receptors is a group of immediate early genes induced by a pleiotropy of stimuli including peptide hormones, growth factors, cytokines, inflammatory, and physiological stimuli, and cellular stress. NR4A receptors function as potent sensors of changes in the cellular microenvironment to control physiological and pathological processes through genomic and non-genomic actions. NR4A receptors control metabolism and cardiovascular and neurological funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 72 publications
2
32
0
Order By: Relevance
“…Five genes were significantly increased (FDR adjusted P < 0.05, log 2 FC > 1.6) following the first Gardnerella exposure ( Figure 3 and Supplemental Table 8 ), and no genes withstood FDR correction after the second Gardnerella exposure. Notably, all of the upregulated genes ( Atf3 , Fosb , Nur77, Nurr1 and Arc ) belong to the class of Immediate Early (IE) response genes that are rapidly co-induced in multiple cell types in response to external stimuli, such as infection and inflammatory signals ( Wilson et al., 2010 ; Bahrami and Drablos, 2016 ; Crean and Murphy, 2021 ). This suggests that the presence of these genes in the dataset was not random or artifactual, but reflects a coordinated rapid response to Gardnerella exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Five genes were significantly increased (FDR adjusted P < 0.05, log 2 FC > 1.6) following the first Gardnerella exposure ( Figure 3 and Supplemental Table 8 ), and no genes withstood FDR correction after the second Gardnerella exposure. Notably, all of the upregulated genes ( Atf3 , Fosb , Nur77, Nurr1 and Arc ) belong to the class of Immediate Early (IE) response genes that are rapidly co-induced in multiple cell types in response to external stimuli, such as infection and inflammatory signals ( Wilson et al., 2010 ; Bahrami and Drablos, 2016 ; Crean and Murphy, 2021 ). This suggests that the presence of these genes in the dataset was not random or artifactual, but reflects a coordinated rapid response to Gardnerella exposure.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, NR4A1 reactivation by its agonist cytosporone B could inhibit IL-1 β induced chondrocyte inflammation, and injection of cytosporone B protected cartilage damage and alleviated osteoarthritis in rat osteoarthritis model [ 24 ]. More importantly, current available research elucidated that NR4A receptors modified the activity of FLSs to regulate synovial tissue hyperplasia, pathological angiogenesis, and cartilage turnover [ 25 ], which indicated that Nur77 might be involved in the progression of RA. Besides, Nur77 was identified as an acetylated protein, and HDAC1 decreased the acetylation level, transcriptional activity, and protein level of Nur77 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, steroid receptors may modify enzymes and ion channels independent of transcriptional activation, namely, nongenomic effects [ 94 ]. Besides metabolic regulation through binding to multiple hormones, NRs also widely impact the embryonic development and maturation of several organ systems, signaling control in proliferation, and reproduction [ 95 ].…”
Section: Transcriptional Regulation Of Lipid Metabolism By Nrs In Nafldmentioning
confidence: 99%